PEDULILINDUNG APPLICATION AS A COMPREHENSIVE COMMUNICATION MANAGEMENT IN INDONESIA - Citra Eka Putri; Radja Erland Hamzah (Moestopo International Review on Social, Humanities, and Sciences, 2022)
The purpose of this study is to find out how government communication management applies the use of the PeduliLindung application during the Covid-19 endemic transition period in Indonesia. This study uses a qualitative descriptive method with in-depth interview and observation data collection methods. The theory used in this study is the theory of communication management of the Matouschka dolls. The results of the study show that the role of opinion leaders is needed so that information can reach the public; interpersonal communication where public awareness and media play an important role in disseminating information; the implementation of the use of the PeduliLindung application as an information system used by the wider community has played a very important role in the transition period of the Covid-19 endemic in Indonesia; Competence in using the PeduliLindung application greatly affects effective communication management during the Covid-19 endemic transition period in Indonesia, how the government is able to increase the level of digital literacy, the more people who use it, the higher the accuracy level, so that we can help others in tackling the spread of Covid-19. 19 in the endemic period.